Total Synthesis of (+)-Cavicularin: The Pyrone Diels–Alder Reaction in Enantioselective Cyclophane Synthesis - Zhao, Peng; Beaudry, Christopher M. (Synlett, 2015)
A pyrone Diels–Alder strategy was developed for the synthesis of the cyclophane natural product, cavicularin. The strategy uses a vinyl sulfone as an alkyne equivalent dienophile. An enantioselective variant delivered (+)-cavicularin.
Keywords: Diels–Alder; pyrone; cyclophane; chirality; total synthesis